Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3109/0886022x.2014.890841
|View full text |Cite
|
Sign up to set email alerts
|

Determination of oxidative stress and cellular inflammation in patients with diabetic nephropathy and non-diabetic nephropathy being administered hemodialysis treatment due to chronic renal failure

Abstract: Objectives: We aimed to evaluate oxidative stress , malondialdehyde (MDA)] endothelial damage [asymmetric dimethylarginine (ADMA)] and markers of cellular inflammation [interleukin 6 (IL-6), tumor necrosis factor-alpha (TNF-a), neopterin (NP) and high-sensitivity C-reactive protein (hsCRP)] in patients with diabetic nephropathy (DN) and non-diabetic nephropathy who were being administered hemodialysis treatment because of chronic renal failure. Methods: In determining 8-OHdG, IL-6 and TNF-a levels, Enzyme-Link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…They showed that serum 8-OHdG was negatively related with estimated GFR and positively was associated with inflammatory markers such as hsCRP, IL-6, TNF, endothelial function marker (VCAM-1) and iron status (ferritin) (14). Avci et al concluded that albumin and hemoglobin had an inverse relation with 8-OHdG which is in agreement with our finding (14,29).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…They showed that serum 8-OHdG was negatively related with estimated GFR and positively was associated with inflammatory markers such as hsCRP, IL-6, TNF, endothelial function marker (VCAM-1) and iron status (ferritin) (14). Avci et al concluded that albumin and hemoglobin had an inverse relation with 8-OHdG which is in agreement with our finding (14,29).…”
Section: Discussionsupporting
confidence: 92%
“…One study has shown the increase in the levels of 8-OHdG (marker of DNA damage) and malondialdehyde (marker of lipid damage) after HD in diabetic nephropathy (DN) and non-DN groups but decrease was observed in the asymmetric dimethylarginine (marker of endothelial damage) levels. This finding needs more attention (29). One study showed that measurement of 8-OHdG in the plasma rather than tissue of diabetic rats is a more useful biomarker of oxidative DNA damage (38).…”
Section: Limitationsmentioning
confidence: 99%
“…[22][23][24][25] The current study assessed lipid peroxidation, antioxidant defenses and trace elements in CRF patients compared with healthy controls. Trace elements such as Se, Zn and Cu are required during several steps in the intermediary metabolism of mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…Low molecular weight uremic toxins are water-soluble compounds with a molecular weight below 0.5 kDa, and consequently are easily removed by dialysis, and do not exert harmful effects on the body (26,27). The most important uremic toxins classified as purine derivatives are: Products resulted from the degradation of purines (adenosine, inosine, xanthine, guanosine, hypoxanthine, guanine, UA), products of guanosine triphosphate catabolism (neopteri n) and oxidative DNA base damage product (8-hydroxy-deoxy-guanosine) (28)(29)(30). The metabolic pathways of purine catabolism imply several phases (31).…”
Section: Introductionmentioning
confidence: 99%